Effect Of Geometry On Stress In Pile Head Of Rc Sheet Pile Under Vertical Impact Load - Lim, Teik Jin (Universiti Sains Malaysia, 2022)
Impact driving is one of the driving systems that applies a series of hammer strikes to drive the sheet pile into the earth. There have been instances reported where pile head is damaged due to the action of impact hammer. The pile head failure causes the difficulty in pile driving. In industry, the pile head is designed through trial-and-error method to reduce the damage. A systematic study with the consideration of different parameters of pile head should be carried out to study the stress distribution within pile head. This is to achieve the best and economical design of pile head in minimizing the damage. LUSAS software is used to simulate the RC sheet pile with the vertical impact load acting on its top. The first analysis is to justify the maximum impact load from the impact of hammer ram based on different approaches. The approaches of stress wave theory and the equation of motion provide a more reasonable magnitude of maximum impact load compared to the dynamic amplification factor. The second analysis is to determine the effect of confinement ratio on stress distribution along the RC sheet pile. The result shows that the effect on the trend of stress distribution is small. The third analysis is to study the effect of geometry on stress in pile head of RC sheet pile under vertical impact load. The result shows that there is no effect of geometry on stress in pile head for the range of pile head parameters considered in this study.